An assessment of health and social-economic status among Lanoh ethnic sub-group of Orang Asli (indigenous peoples) in Air Bah I village, state of Perak, Malaysia - Yi Xin Cheng, Chee Ping Chong, Chai Fung Kiew, Mohd Baidi Bahari (Journal of Applied Pharmaceutical Science, 2014)
This study was conducted to assess the health and social economic status of Lanoh ethic sub-group of Orang Asli (indigenous peoples) in Air Bah I village, Malaysia. A one day study which involved health screening and structured interview was conducted on 16 April 2011. Forty five Orang Asli participated in the health screening. Fifteen subjects were newly discovered to have high blood pressure while 5 subjects had high blood glucose level. Only 37.8 % had normal body mass index and 26.7 % were pre-obese. Thirteen subjects were interviewed about their health seeking behavior and knowledge of the proper use of medications. Slightly more than half (53.8 %) of the subjects was uneducated and 69.2 % were rubber tappers with the median monthly household income of RM 400 (USD 122.31). Approximately 77 % of the subjects had visited the health centre for body checkups. The utilization of herbs as medications (23.1 %) was common and the majority (76.9 %) said that traditional medications were safe compared to modern medications. Around 46 % of Orang Asli had the opinion that medications should be kept in the refrigerator and exposed places and 61.5 % shared medications with others. In conclusion, the Lanoh are still categorized under the poverty group and their education level remains low. Therefore, education intervention is necessary to improve their knowledge on the proper use of medications.
Keywords: Orang Asli, indigenous peoples Malaysia, health status, health seeking behavior, social-economic status.